2005
DOI: 10.1002/eji.200526065
|View full text |Cite
|
Sign up to set email alerts
|

Reduced suppressive effect of CD4+CD25high regulatory T cells on the T cell immune response against myelin oligodendrocyte glycoprotein in patients with multiple sclerosis

Abstract: Immunoregulatory T cells of CD4 + CD25 + phenotype suppress T cell function and protect rodents from organ-specific autoimmune disease. The human counterpart of this subset of T cells expresses high levels of CD25 and its role in human autoimmune disorders is currently under intense investigation. In multiple sclerosis (MS), a chronic inflammatory disease of the central nervous system (CNS), the activation of circulating self-reactive T cells with specificity for myelin components is considered to be an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
292
7
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 398 publications
(346 citation statements)
references
References 41 publications
32
292
7
9
Order By: Relevance
“…Accordingly, the frequency of CD95ϩ Treg in whole PBMC fractions in patients with CLE was not lower than that in normal healthy donors. We also did not observe increased CD95L-mediated cell death or enhanced CD95 expression in a cohort of patients with newly diagnosed multiple sclerosis (30). Therefore, the question remains open whether enhanced sensitivity to apoptosis of Treg can contribute to autoimmune diseases.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Accordingly, the frequency of CD95ϩ Treg in whole PBMC fractions in patients with CLE was not lower than that in normal healthy donors. We also did not observe increased CD95L-mediated cell death or enhanced CD95 expression in a cohort of patients with newly diagnosed multiple sclerosis (30). Therefore, the question remains open whether enhanced sensitivity to apoptosis of Treg can contribute to autoimmune diseases.…”
Section: Discussioncontrasting
confidence: 55%
“…CD4ϩ,CD25 high Treg and CD4ϩ,CD25 low /CD4ϩ,CD25 Ϫ Treg were isolated from the pure, untouched CD4ϩ T cells using CD25 magnetic beads (Miltenyi Biotech). Titration of magnetic beads and optimization of further conditions (temperature, column flow rate, incubation time) allowed for a more rapid Treg isolation (Ͻ2 hours) than that achieved with FACS, at a similar purity of at least 82% (30). Further characterization of magnetically isolated Treg showed a suppressive capacity similar to that of Treg sorted by FACS and similar levels of Foxp3 expression, as determined by quantitative reverse transcription-polymerase chain reaction (data not shown).…”
Section: Methodsmentioning
confidence: 91%
“…TGFb is a cytokine known to be particularly important in the development and function of regulatory T cells (Tregs) (Yamagiwa et al, 2001;Zheng et al, 2002;Chen et al, 2003), protectors against autoimmune responses (Suri-Payer et al, 1998;Itoh et al, 1999;Sakaguchi, 2004). Tregs in patients with multiple sclerosis, while normal in number, demonstrate diminished suppressive effect on myelin-specific autoreactive T cells, low FOXP3 expression, and a less diverse T cell receptor (TCR) repertoire (Viglietta et al, 2004;Haas et al, 2005Haas et al, , 2007Huan et al, 2005;Kumar et al, 2006;Venken et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This result is of potentially important clinical value since T reg function is known to be impaired in patients with MS 1, 2, 3. Since suppressive function often corresponds to the production of IL‐10, we next determined if stimulation with PSA resulted in an increase in IL‐10 production.…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that the fluctuation between relapse and remission is greatly influenced by the balance of self‐reactive effector T cells and regulatory T cells (T regs ). Importantly, studies have shown that while MS patients harbor normal frequencies of T regs , their production of IL‐10 and overall suppressive capacity is significantly reduced allowing for increased inflammation driven by effector cells 1, 2, 3. For many years, the immunopathogenesis of this condition was attributed to an imbalance of Th1/Th2 polarization in which the enhanced Th1 response was associated with the production of IFN γ and TNF α .…”
Section: Introductionmentioning
confidence: 99%